Damai dalam Penyelesaian Sengketa Wan Prestasi (Kajian Hadis tentang Damai pada Fatwa DSN MUI No. 08/DSN-MUI/IV/2000) - Jihan Nahda Nafiah; Isabel Zalita Putri; Miftahul Ubaidilah (El-Sunnah)
Resolving non-performance disputes is an essential process in creating peace. Through an inclusive and dialogue-based approach, the parties involved can reach a just and sustainable solution. This settlement not only includes legal aspects, but also promotes mutual understanding, collaboration and reconciliation. Thus, building peace in resolving non-performance disputes is a crucial step in realizing harmony and sustainability in relationships between individuals or groups. In this study, the research used a qualitative method where the way to obtain data was by library research. Based on this description, the dispute issue that will be studied and analyzed in this article is related to the interpretation of the peace hadith in efforts to resolve non-performance disputes